Bankers as immoral? Some parallels and differences between Aquinas's views usury and Marxian views of banking and credit - Thomas Lambert (Economic Thought, 2023)
Since ancient times the practices and ethics of bankers and banking in general have undergone a great deal of criticism. While lending is motivated by profit, and while households are not explicitly coerced into borrowing money, the justice of a system which exploits workers and at the same time encourages them to borrow money in order to maintain a certain standard of living can be viewed as sometimes unfair and perhaps immoral. The value of goods, according to St. Thomas Aquinas and Karl Marx, should mostly reflect the value of labor embodied in them, and for that reason, labor should be compensated fully for its work. For these reasons, Aquinas and Marxian economists offer somewhat similar and at the same time different views on both the labor theory of value as well as on the morality of certain banking practices. If credit and the banking system also bring about crisis and the greater concentration and centralization of capital, then the morality of these outcomes also needs to be examined.
Keywords: B11; B51; N20; 330; Banking; exploitation; usury; Aquinas; Marx